American Stravinsky The Style and Aesthetics of Copland's New American Music, the Early Works, 1921-1938 - Murchison, Gayle (University of Michigan Press, 2012)
One of the country's most enduringly successful composers, Aaron Copland created a distinctively American style and aesthetic in works for a diversity of genres and mediums, including ballet, opera, and film. Also active as a critic, mentor, advocate, and concert organizer, he played a decisive role in the growth of serious music in the Americas in the twentieth century. In The American Stravinsky, Gayle Murchison closely analyzes selected works to discern the specific compositional techniques Copland used, and to understand the degree to which they derived from European models, particularly the influence of Igor Stravinsky. Murchison examines how Copland both Americanized these models and made them his own, thereby finding his own compositional voice. Murchison also discusses Copland's aesthetics of music and his ideas about its purpose and social function.